2022
DOI: 10.3389/fcell.2022.1046248
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and the primary cilium in cell metabolism: What’s upstream?

Abstract: The maintenance of cellular homeostasis in response to extracellular stimuli, i.e., nutrient and hormone signaling, hypoxia, or mechanical forces by autophagy, is vital for the health of various tissues. The primary cilium (PC) is a microtubule-based sensory organelle that regulates the integration of several extracellular stimuli. Over the past decade, an interconnection between autophagy and PC has begun to be revealed. Indeed, the PC regulates autophagy and in turn, a selective form of autophagy called cili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 147 publications
0
1
0
Order By: Relevance
“…These forces are transduced by mechanosensors present at the cell surface, such as piezo receptors, microvilli, and the primary cilium [21][22][23]. Recent studies have shown that the primary cilium transduces mechanical forces to stimulate autophagy in different organs, especially in the kidney [24][25][26][27].…”
mentioning
confidence: 99%
“…These forces are transduced by mechanosensors present at the cell surface, such as piezo receptors, microvilli, and the primary cilium [21][22][23]. Recent studies have shown that the primary cilium transduces mechanical forces to stimulate autophagy in different organs, especially in the kidney [24][25][26][27].…”
mentioning
confidence: 99%